Global frequency of benign and malignant odontogenic tumors according to the 2005 WHO classification - Silva, Leorik Pereira da; Macedo, Rômulo Augusto de Paiva; Serpa, Marianna Sampaio; Sobral, Ana Paula Veras; Souza, Lélia Batista de (Journal of Oral Diagnosis, 2017)
Odontogenic tumors are a heterogeneous group of lesions with variable clinical behavior. This manuscript aimed to determine the global frequency and distribution of OT based on the 2005 WHO classification. The manuscript performed a systematic search conduc- ted in only one database (PubMed/Medline). We identified 8,658 articles, of which 495 articles were evaluated. After applying the inclusion and exclusion criteria, 42 papers were selected. Summed up, a total of 13,490 cases of OT were diagnosed. Most cases were found in Asia (n=6,472) and North America (n=2,599). Keratocystic odontogenic tumor (KCOT) (32.1%) was the most frequent neoplasm, followed by ameloblastoma (AMB) (30.6%) and odontoma (ODO) (17.3%). Malignant tumors were uncommon, accounting for 4.7% of all tumors. Of those, malignant ameloblastoma (n=184) and ameloblastic car- cinoma (n=115) were the most common tumors. Overall, OT were more prevalent in men (n=4,896), with a male:female ratio of 1.2:1. The age ranged from 1 to 92 years; however most tumors occurred between the second and fourth decades of life. The mandible was the most common anatomical site, with a mandible:maxilla ratio of 2.8:1. The prevalence profile of OT shows a geographical variation; moreover, studies based on prior WHO classifications present a different incidence and frequency. The 2005 WHO classification of OT altered the distribution of these lesions and possibly made KCOT the most common OT observed worldwide.